(untitled) (Práxis Educativa, 2025)
This study thematizes some meanings implied in the teaching of Philosophy within the social, epistemological, and educational scenario of liquid modernity. The hypothesis revolves around the idea that there is a social transition from a scenario of solid modernity to liquid modernity, which produces a crisis in the educational context, changing the way the meaning of Philosophy teaching at school is conceived. Thus, there is a new social condition in which new meanings and senses emerge regarding the art of educating and being an educator. The study was built based on a theoretical-methodological approach of hermeneutic and critical-dialectical background, addressing three fundamental dimensions that are constitutive of the pedagogical activity involving the teaching of Philosophy in schools. These dimensions refer to the problematic of knowledge and teaching intervention, with regard to their relations with subjectivity, knowledge paradigms, and historical-social changes. Keywords: Philosophy teaching. Education. Liquid modernity.